Expression of HLA-DR antigens by colonic epithelium in inflammatory bowel disease. - Selby, W; Janossy, G; Mason, D; Jewell, D (1983)
The expression of HLA-DR and HLA-A,B,C antigens by human colonic epithelium has been examined in tissue sections of patients with inflammatory bowel disease using an immunohistological technique. Colonic epithelial cells from all 21 control subjects with histologically normal colonic mucosa were HLA-DR-. In contrast, in nine of 13 patients with active ulcerative colitis and 11 of 12 with active Crohn's disease the epithelium of involved colonic mucosa was HLA-DR+. HLA-DR antigens were found on the epithelium of only one of six patients with ulcerative colitis in remission and one of three with inactive Crohn's disease. Moreover, these antigens were not present on the epithelium of non-inflamed colonic mucosa in two patients with Crohn's disease in whom adjacent involved mucosa showed strong epithelial reactivity. This difference between patients with active and those with inactive disease is highly significant (P less than 0.005). These findings provide further evidence of the importance of cell-mediated immune mechanisms in the pathogenesis of inflammatory bowel disease.